2014
DOI: 10.7763/ijfcc.2014.v3.333
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Botnets Development: Issues and Solutions

Abstract: Abstract-Due to their limited capabilities, mobile devices have rarely been adopted as attack vectors. In this paper, we consider the execution of coordinated and distributed attacks perpetrated by mobile devices (mobile botnet). We first describe current botnets architectures, analyzing their strengths and weaknesses. Then, we identify problems deriving from the development of a mobile botnet. Appropriate solutions to such problems have been proposed, thus providing an important resource during design and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In recent times, mobile botnet has become the destination of bot-master and this is due to the proliferation of internet oriented mobile devices. In a work done by Farina et al [18] it was revealed that " the development and diffusion of mobile devices such as smart phones with internet accessibility through Wi-Fi, 3G, LTE, etc " has given the needed technique for mobile devices attack. They also proposed in the same article that adequate attention be given to the development of mobile botnet protection.…”
Section: Fig 1 Computer Communication With Adherence To Osi/iso Modmentioning
confidence: 99%
“…In recent times, mobile botnet has become the destination of bot-master and this is due to the proliferation of internet oriented mobile devices. In a work done by Farina et al [18] it was revealed that " the development and diffusion of mobile devices such as smart phones with internet accessibility through Wi-Fi, 3G, LTE, etc " has given the needed technique for mobile devices attack. They also proposed in the same article that adequate attention be given to the development of mobile botnet protection.…”
Section: Fig 1 Computer Communication With Adherence To Osi/iso Modmentioning
confidence: 99%
“…A dysfunctional device can cause the failure of a whole IoT-based system. Furthermore, although each device has limited capabilities, recent studies [30,31] show that the compromised devices can be organized into a mobile botnet conducting more sophisticated attacks. However, more than 200,000 devices in 2017 still require a software patch against the Heartbleed attack that occurred in 2014 [32].…”
mentioning
confidence: 99%